Empirical Antibiotic for Diabetic Foot Infection in Indonesian Tertiary Hospital, Is It Time to Rethink the Options? - Hikmat Permana; Aluisha Saboe; Nanny NM Soetedjo; Dewi Kartika; Bachti Alisjahbana (Acta Medica Indonesiana)
Background: The choice of empiric antibiotics in Diabetic Foot Infection (DFI) is a key to successful therapy. Meanwhile, the management of DFI in Indonesia is  based on guideline originating from western countries which have different bacteriological patterns. Therefore, this study aimed to describe the bacterial and antibiotic susceptibility pattern on DFI which potentially contribute to better antibiotics selection guidelines. Methods: This was a cross-sectional descriptive study conducted using consecutive sampling with DFI patients admitted in the emergency room and wards of Hasan Sadikin Hospital between February and July 2020. Tissue samples were obtained from all wounds, while antibiotic susceptibility tests were carried out on the culture results. Results: A total of 65 bacterial growths were obtained from 45 enrolled patients. Gram-negative bacteria dominated with 54 growths (83.07%) including Klebsiela pneumonia 13 (20%) as the most common. Furthermore, antibiotics with good susceptible (> 80%) against Gram-negative bacteria are the carbapenemes (meropenem and ertapenem) and amikacin. The multi drug resistant bacteria were found in 18 growths (27.7%), which include ESBL, Carbapenemase producing bacteria, and MRSA. However, there were no susceptibility pattern differences between patients with ulcer duration above or below 2 months, higher grade wound (Wagner 4 and 5) and lower, as well as patients with previous or no antibiotic history. Conclusion: The growth of Gram-negative bacteria dominated DFI with limited susceptibility to the empirical first-line antibiotics in the known international guidelines. Therefore, there is a need to reconsider the algorithm for selecting empirical antibiotics and management of DFI which is appropriate in our current condition.